Counterinsurgency and its discontents: Assessing the value of a divisive concept - David Ucko (Stiftung Wissenschaft und Politik (SWP), 2011)
Popularised as a result of the so-called surge in Iraq, the concept of counterinsurgency has since experienced a marked decline, mostly due to the difficulties of implementing its core principles in Afghanistan. Across the United States and Europe, counterinsurgency now seems to be on its way out, as a concept to be studied and as a priority to inform policy. This article examines the value of retaining counterinsurgency as a concept, along with its associated principles and theory. Much depends on what is expected from this term, which lacks both definition and clear substance. Counterinsurgency provides neither a strategy for military intervention nor a campaign plan for deployed soldiers and will fail if mistaken for more than what it is. Counterinsurgency does offer a collection of insights, which, if used in a manner sensitive to local context, can help in the design and execution of expeditionary campaigns. These insights are often largely commonsensical but have nonetheless played an important role in challenging previously dominant misconceptions about the nature of war and peace, both in Europe and the United States. The one good reason to abandon the term would be because of its divisive and distorting connotations; the aim then would be to talk more plainly about the nature of war-to-peace transitions. Even so, expunging counterinsurgency from the lexicon will not remove or in any way alleviate the operational challenges most closely associated with it. Thus, whatever happens to this concept, the lessons and associated theory that it has advanced must not be forgotten. Instead, these must be retained to prepare expeditionary actors for future military interventions and, at the same time, to prompt far greater caution whenever such endeavours are planned
Keywords: 320